The Magic World of Storytelling: Some Points for Reflection - Castro Martha (Profile: Issues in Teachers' Professional Development)
There are many ways to get students involved in the English learning process. Telling stories is one of the most effective ones. This article attempts to gather some pedagogical and psychological reasons why this kind of activity is important, not only to improve students vocabulary and make them achieve a feeling of self confidence but to let them develop social values.